Vehicle to grid connected technologies and charging strategies: Operation, control, issues and recommendations - Hannan M.A.; Mollik M.S.; Al-Shetwi A.Q.; Rahman S.A.; Mansor M.; Begum R.A.; Muttaqi K.M.; Dong Z.Y. (Elsevier Ltd, 2023)
Charging (batteries); Electric load flow; Electric power system control; Electric power transmission networks; Plug-in electric vehicles; Plug-in hybrid vehicles; Reactive power; Virtual storage; Bidirectional power flow; Charging infrastructures; Charging strategies; Grid operators; Grid-connected; Operations control; Power grids; Technology strategies; Unidirectional/bidirectional power flow; Vehicle to grids; Vehicle-to-grid